A STUDY OF THE EFFECT OF PERCEIVED TRAINING AND DEVELOPMENT ON EMPLOYEE PERFORMANCE AT SELECTED HOTELS IN SARAWAK - Lau Hui Lin; Lee Jian Yang (Jurnal Penyelidikan Sains Sosial, 2020)
This paper examined on the perception of employees on training and development toward employee performance at hotels located in the middle of region of Sarawak. The purpose of this research paper is to determine the relationship between training & development and employee performance among staff in hotels. The quantitative analysis method of a primary source was utilized to collect the data from 150 staff respondents. Five Likert scales were used to measure the degree of training and employee performance. A total of 112 responses were analysed using SPSS version 23.0. The results of this study revealed that training and development has a significant positive influence on employee performance and there is a significant relationship between training and employee performance. Most importantly, on the job training was perceived as a popular job training method used to improve employee performance and it is considered as one of the effective job training methods helped to improve employee performance as proven in many researches and studies. This study also suggested that Human resource management at hotels should develop an effective training programmes to improve employee performance and employees need to be informed of the training benefits ahead of the training since training is a supportive strategic tools assist organization and employee success in the future competitive environment. Moreover, this study also contributes to a better understanding of the effect of training on employee job performances among hotels in Sarawak. The implications for practice and suggestions for future research are also discussed